Tunable intracrystal cavity in tungsten bronze-like bimetallic oxides for electrochromic energy storage - Cai, Guofa (2022)
Designing materials with appropriate crystal and electronic structures to enhance ionic and electronic transport simultaneously are highly desirable for both electrochromic and electrochemical energy storage devices. It remains a great challenge to simultaneously meet these requirements. Here, a Nb18W16O93 nanomaterial is successfully synthesized with superstructure motifs and uniform self-supported electrochromic films are prepared on a transparent conductive substrate. The results show that the films can effectively accommodate lithium ions and facilitate intercalation–deintercalation on transparent fluorine-doped tin oxide (FTO) substrates at high current density. Mechanistic insights into the excellent electrochromic and rechargeable energy storage properties are provided by density functional theory (DFT) calculations. Specifically, the Nb18W16O93 film displays a large optical modulation (up to 93% at 633 nm and 89% at 1200 nm), high coloration efficiency (105.6 cm2 C−1), high energy storage capacity (151.4 mAh g−1 at 2 A g−1), excellent rate capability, and long-term electrochemical stability (6000 cycles). As a demonstration of its application, an energy storage indicator is illustrated and a complementary electrochromic energy storage smart window is fabricated based on the Nb18W16O93 film. The results demonstrate that the Nb18W16O93 nanomaterial has a promising application in the field of high-performance electrochromic and energy storage devices.